Large Scale Generation and Characterization of Anti-Human CD34 Monoclonal Antibody in Ascetic Fluid of Balb/c Mice - Aghebati Maleki, Leili (Tabriz University of Medical Sciences, 2013)
Purpose: Monoclonal antibodies or specific antibodies are now an essential tool of biomedical research and are of great commercial and medical value. The purpose of this study was to produce large scale of monoclonal antibody against CD34 in order to diagnostic application in leukemia and purification of human hematopoietic stem/progenitor cells. Methods: For large scale production of monoclonal antibody, hybridoma cells that produce monoclonal antibody against human CD34 were injected into the peritoneum of the Balb/c mice which have previously been primed with 0.5 ml Pristane. 5 ml ascitic fluid was harvested from each mouse in two times. Evaluation of mAb titration was assessed by ELISA method. The ascitic fluid was examined for class and subclasses by ELISA mouse mAb isotyping Kit. mAb was purified from ascitic fluid by affinity chromatography on Protein A-Sepharose. Purity of monoclonal antibody was monitored by SDS -PAGE and the purified monoclonal antibody was conjugated with FITC. Results: Monoclonal antibodies with high specificity and sensitivity against human CD34 by hybridoma technology were prepared. The subclass of antibody was IgG1 and its light chain was kappa. Conclusion: The conjugated monoclonal antibody could be a useful tool for isolation, purification and characterization of human hematopoietic stem cells.